1987
DOI: 10.2136/sssaj1987.03615995005100060045x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Combinations of Triple Superphosphate and a Reactive Phosphate Rock on Yield and Phosphorus Uptake by Corn

Abstract: A combination of finely ground phosphate rock (PR) and triple superphosphate (TSP) represents a method that can improve the agronomic value of PR at a lower cost than would be required to manufacture the conventional, fully acidulated fertilizers from that same rock. A reactive PR from North Carolina was evaluated for its effectiveness as a P source when used in conjunction with TSP at P rates up to 266 mg P kg−1 in a short‐term (6‐week) greenhouse experiment. The soil used was a limed Mountview silt loam (Typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
1
4

Year Published

1989
1989
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 0 publications
3
17
1
4
Order By: Relevance
“…4, a single curve was able to fit the data points from the check, PAPR, and SSP obtained in the two soils (Savannah T and Venago + Fe-gel) with lowest and highest P-fixing capacity. A similar relationship was also reported by Chien et al (1987), in which the internal efficiency of TSP was the same as that of a mixture of TSP and PR (North Carolina) with a P rate at 50:50. In the latter study, the internal efficiency of PR was found to be lower than that of TSP.…”
Section: Resultssupporting
confidence: 84%
“…4, a single curve was able to fit the data points from the check, PAPR, and SSP obtained in the two soils (Savannah T and Venago + Fe-gel) with lowest and highest P-fixing capacity. A similar relationship was also reported by Chien et al (1987), in which the internal efficiency of TSP was the same as that of a mixture of TSP and PR (North Carolina) with a P rate at 50:50. In the latter study, the internal efficiency of PR was found to be lower than that of TSP.…”
Section: Resultssupporting
confidence: 84%
“…Another probable explanation for this interaction is the initial effect caused by the water-soluble P that would lead to higher plant uptake of P from PR due to better root system development (Chien et al, 1987).…”
Section: Resultsmentioning
confidence: 99%
“…As an alternative to the use of superphosphates, phosphate rocks or an association of both sources can be used to manage P fertilization with sources presenting distinct solubility traits (Chien et al, 2009). The joint utilization of these sources can be either accomplished by applying combinations of phosphate rock and soluble sources (Chien et al, 1987;Franzini et al, 2009aFranzini et al, , 2009bNachtigall et al, 1989;Menon et al, 1991;Prochnow et al, 2004b;Villanueva et al, 2006) or by applying them separately but in the same area (associated use).…”
Section: Introductionmentioning
confidence: 99%
“…Acidulation, Partial acidulation , Blending with sulphur (Rajan 1982(Rajan , 1983(Rajan , 1987, Heap leaching (Habashi 1989(Habashi , 1994, Blending and granulation (Lupin and Le 1983, Chien et al 1987, Chien and Menon 1995a (Lai and Eberl 1986).…”
Section: Chemical Modificationmentioning
confidence: 99%